ECOSSISTEMAS DE INOVAÇÃO LOCAL PARA O DESENVOLVIMENTO DO AGRONEGÓCIO EM CAMPO GRANDE E DOURADOS - Luciene dos Santos Errobidart Mattos (2022)
In the context of economic studies, the issue of innovation demonstrates a new form of technical production system, in addition to adding and generating value to the service. In the current scenario, it represents competitiveness, economic growth and development and integrates scientific and technological development, the links between academia, companies, and government. Based on the assumptions about innovation by Joseph Schumpeter and the Organization for Economic Cooperation and Development (OECD), we seek to understand innovation ecosystems, focusing on agribusiness (livestock and agriculture) in the municipalities of Campo Grande and Dourados, at Mato Grosso do Sul. Both municipalities were identified by the SEBRAE(2019) methodology as highlights in agribusiness and innovation. The initial objective is to analyze how agribusiness ecosystems established at the chosen cities, considering that agribusiness productivity is a process of improving management and focusing on the market with the benefit/performance of innovation. Thus, from a reading that aims to observe the operation in the Triple Helix, the initial mapping of the ecosystems of the municipalities presented, as well as their respective levels of maturity, as well as the integration of local actors and the effectiveness of their actions towards innovation. The results have discussions about the relationship between ecosystems with the agribusiness, as well as the influence of these ecosystems at Campo Grande and Dourados, and public policies aimed at innovation in agribusiness.